Pathway Control in Cooperative vs. Anti‐Cooperative Supramolecular Polymers. (4th July 2019) - Herkert, Lorena; Droste, Jörn; Kartha, Kalathil K.; Korevaar, Peter A.; de Greef, Tom F. A.; Hansen, Michael Ryan; Fernández, Gustavo
Abstract: Controlling the nanoscale morphology in assemblies of π‐conjugated molecules is key to developing supramolecular functional materials. Here, we report an unsymmetrically substituted amphiphilic Pt II complex 1 that shows unique self‐assembly behavior in nonpolar media, providing two competing anti‐cooperative and cooperative pathways with distinct molecular arrangement (long‐ vs. medium‐slipped, respectively) and nanoscale morphology (discs vs. fibers, respectively). With a thermodynamic model, we unravel the competition between the anti‐cooperative and cooperative pathways: buffering of monomers into small‐sized, anti‐cooperative species affects the formation of elongated assemblies, which might open up new strategies for pathway control in self‐assembly. Our findings reveal that side‐chain immiscibility is an efficient method to control anti‐cooperative assemblies and pathway complexity in general. Abstract : Die Unvermischbarkeit von Seitenketten erlaubt die volle Kontrolle über die Bildung einer hoch stabilen diskreten anti‐kooperativen Anordnung, die in Konkurrenz zur Bildung kooperativer supramolekularer Polymere steht. Dies ermöglicht neue Strategien für die Kontrolle über den Reaktionspfad in Selbstorganisationsprozessen.